Experimental Research of Formation of the Future Clothes Designers Professional Competency - Saprykina, Liliya (Pedagogical Discourse, 2014)
The article pays attention to the necessity of increasing knowledge level of students taking into account specification specificity of professional activity of the future clothes designers. The attention was concentrated on the analysis of results of the process of formation professional competence of the future clothes designers. The methods of carrying out pedagogical experiment have been revealed. The extended characteristics of stages of experimental work as for formation professional competence of the future clothes designers. The complex of diagnostic methods of research of formation professional competence of future clothes designers’ state during learning professional disciplines was presented. It was found out the significance of structural components of professional competence through researching their formation among future clothes designers. The level of readiness of basic and practical knowledge, skills and abilities of the future clothes designers was defined. The level of forming individual-psychological, professional-personal qualities of students was evaluated. The level of self-evaluation and reflection of the future clothes designers was identified. According to quantitative and qualitative analyses the estimation and analysis of data of initial level of forming professional competence was done. The results of implementation of methods of professional competence were offrered. The dynamics of levels of professional competence of the future clothes designers after carrying out of the experiment was demonstrated and analyzed. The efficiency of step-by-step implementation of tyh method of formation of professional competence was identified.